Adapted part design methods for springback minimization of stamped sheet metal car body components. Issue 1 (June 2021) - Birkert, A; Dreiseitel, F; Hartmann, B; Held, T; Hetterle, O; Markin, M; Scholle, M
Abstract: In sheet metal forming, both the dimensional accuracy of the manufactured parts and the robustness of the forming process are significantly compromised by elastic springback effects. In contrast to traditional compensation methods mostly relying on modifications of the tool geometry, a part geometry-based approach reduces the amount of springback by appropriately manipulating the part stiffness through slight modifications of the part geometry. To date, part-geometric measures are mostly based on practical experience and trial-and-error processes resulting in a need for simple and effective simulation-based approaches. In the present work three novel simulation-based approaches for a suitable modification of structural component design are suggested relying on unconventional topology optimization, the so-called line-of-force method and shape optimization . First tests with a classical hat profile reveal that the optimized geometries, compared to the nominal one, lead to significant reductions of the springback after stamping and simultaneously to a notable decrease of the process variation when parameters of the forming process are varied slightly. For the adapted topology optimization approach the excellent results are also confirmed when applied to the industry-relevant case of a truck rear panel.